Risk assessment for bluetongue virus spread in Kazakhstan - Zhigailov, A.V.; Ostapchuk, Y.O.; Perfilyeva, Y.V.; Abdolla, N.; Matseva, E.R.; Naizabayeva, D.A.; Kuatbekova, S.; Mashzhan, A.; Nizkorodova, A.S.; Berdygulova, Zh.A.; et al. (Fundamental and Experimental Biology, 2022)
Kazakhstan is considered to be free from bluetongue. At the same time, biting midges of the genus Culicoides, which are the main vectors of the bluetongue virus, are widespread in the country. An optimal climate for biting midge breeding, a high density of livestock susceptible to the virus, and a constant influx of imported breeding stock from areas where the infection is endemic in southern Kazakhstan cumulatively constitute favorable conditions for the spread of bluetongue in the case of virus transmission in Kazakhstan from other countries. The uncontrolled spread of this infection on the territory of Kazakhstan can be associated with colossal economic losses since sheep breeding is paramount for domestic animal husbandry. In this case, economic costs will not be limited only by the death of animals; significant damage can be caused to the image of our country as an exporter of lamb. This review provides information highlighting the importance of bluetongue control programs in Kazakhstan and an analysis of the risks of the spread of this infection in the country.